Development Of Research Methods for Determining the Operational Characteristics of Electric Vehicles in The Conditions of a Hot Climate of Uzbekistan - Soyib Ortikovich Narziev; Jamshed Sadulloevich Avliyokulov; Shavkat Pirmuxamedovich Alimuxamedov; Zavkiddin Zayniddinovich Sharopov (Zien Journals, 2021)
This article analyzes the changes in the indicators of internal combustion engines in the hot climate in the exploitation of vehicles, the distribution of heat flow in the details of the cylinders when the piston bottom and the touch surface of the cylinder Gorlovka are dry, changes in their temperature and cracks in the piston-cherry Junction and operational characteristics of internal combustion engines
Keywords: Operational characteristics of internal combustion; exploitation of vehicles; indicators; engines